Caracterização limnológica e análise da comunidade de macro-invertebrados bentônicos em um trecho da sub-bacia do alto Rio São Francisco (MG, Brasil) - Affonso, Ana Lucia Suriani (Universidade Federal de São Carlos, 2010)
In lotic environments, the benthic fauna is generally well developed and constitutes a community of great importance in the functioning of these ecosystems. The benthic macroinvertebrates participate in food chains, mineralization processes, recycling of organic matter, energy flow and therefore are useful in the monitoring of environmental quality. The purpose of this study was to analyze the limnological characteristics and their influence on the structure and diversity of macroinvertebrate benthic in a stretch of the Upper São Francisco River and its tributary, Piumhi River. The samplings were carried out in two climatic periods, the dry season (October 2006 and 2007) and the rainy season (March 2007 and 2008), sampling up three points in Piumhi River and six points in São Francisco River. Based on the limnological data the rivers can not be considered eutrophic, presenting relatively low levels of nutrients (total and dissolved). The waters of both rivers studied showed trophic state ranging from ultraoligotrophic to oligotrophic. The sediments of São Francisco River was predominantly formed by sand and clay whereas the sediment of Piumhi River was mainly formed by sand. On October 2006, March 2007, October 2007 and March 2008 there were 19, 14, 44 and 7 taxa in Piumhi River and 29, 42, 36 and 31 taxa in São Francisco River, respectively. There were greater richness of taxa and diversity of benthic macroinvertebrates in São Francisco River than in Piumhi River, whereas regarding the numerical abundance the opposite was verified. The only constant taxa were Polypedilum in Piumhi River (October 2006) and Smicridea in São Francisco River (March 2007). In both rivers, the highest values of abundance and density were recorded for the family Chironomidae during dry periods. Phyllocycla and Gomphoides showed highest values of biomass in Piumhi and São Francisco Rivers, respectively, evidencing their potential to transfer energy to other levels of the food chain and the need to utilize different metrics for studying communities. In Piumhi River there were 7 functional trophic groups while in São Francisco River only 5 groups were recorded, being collectors the dominant groups in both rivers. There was a greater similarity between the macroinvertebrates assemblages within each river sampled in the four periods, than between the rivers studied. The canonical correlation analyses evidenced that sediment characteristics and limnological variables were the principal factores that influenced the distribution of Chironomidae genera.
Keywords: Limnologia; Ecologia de rios; Macroinvertebrados bentônicos; Diversidade biológica; Água - qualidade; CIENCIAS BIOLOGICAS::ECOLOGIA